KARAKTERISTIK, FAKTOR PENDORONG DAN DAMPAK PEREMPUAN MENJADI TKW LUAR NEGERI DI KECAMATAN MRANGGEN KABUPATEN DEMAK. - Munandar, Moh Aris (Faculty of Social Science, Universitas Negeri Semarang, 2013)
This research is motivated by the widespread of village women who wish to work as migrant workers. Data from the Department of Employment and Transmigration PPKLN in 2007 showed that the number of women migrant workers had reached 4 million people , an increase of 25 % per year where 78.3 % work as domestic workers . This phenomenon can also be seen by the increasing number of Indonesian Manpower Services Company (agency) opening its branch in villages. Problems examined in this study is what kind of characters attached to women who are willing to work as migrant workers abroad , both physically as level of education , skill level , who is invited and how she could be willing to work as migrant workers abroad, the status in the household , and non-physical character as mental resiliance. This study used descriptive qualitative research methods. Data were analyzed by using Weft QDA taxonomy. Women workers who work abroad are more likely elementary and junior high school graduates than and senior high school or university graduates . This is due to the fact that foreign consumers are more likely to make them work in informal sector than the formal one. Women migrant workers have the following problems : a ) problem of skills , b ) problem of departure money, c ) problem in the destination country, d ) problems of law protection, and e ) financial management problems. Departure money for women migrant workers is more likely to be obtained by either an individual loan or bank loan. Some of them also sell agricultural land to finance their overseas departure . The success of women migrant workers can be seen from how they can pay off their debts, and how their income can be used for productive activities.